Extraction of Copper from Aqueous Sulfate medium using microcapsule coated with Cyanex 301 - Yeoh Choon Nai (Universiti Malaysia Perlis, 2008)
The copper extraction with the microcapsules containing Cyanex 301 which prepared by solvent evaporation method was study. Gum arabic as dispersion stabilizer and dichloromethane as solvent are used in microcapsules preparation. Gum arabic shows a good formability of microcapsules than gelatin does. The effect of sulfuric acid (H2SO4) molarity, temperature, and amount of microcapsules in copper extraction were investigated. The experimental results show that the percentage copper extraction could be reached optimum (97.72%) at 0.3M of sulfuric acid (H2SO4). The enthalpy of copper extraction to be found is exothermic as the extraction decreased when temperature increased. High microcapsules amount led to higher percentage recoveries. It is concluded that polystyrene microcapsules containing Cyanex 301 can effectively be used in copper extraction.